Pengaruh Efektivitas Penerapan Standar Akuntansi Pemerintahan Terhadap Kualitas Laporan Keuangan Pada Kantor Kementerian Agama Kabupaten Bone - Andi Sari Ayu Juniarti S; Muhammad Yamin; Masyhuri (PT. Hasba Edukasi Mandiri, 2025)
The purpose of this study was to determine the effect of the Application of Government Accounting Standards on the Quality of Financial Statements. This type of research is quantitative research with data collection through questionnaires, samples were taken 36 respondents with simple linear regression test techniques. This study uses primary data obtained from respondents' answers in the form of filling out questionnaires, namely data obtained directly from the object of research. The results of research that has been conducted related to the effect of the effectiveness of the application of government accounting standards on the quality of government financial reports show that the significance test also shows that the t value (3.946) is greater than the t table value (2.032) and the significance value (0.000) is smaller than 0.05. Therefore, the variable effectiveness of the application of government accounting standards on the quality of government financial statements has a positive and significant effect on the quality of government financial statements. Based on the results of the coefficient of determination (R-Square) obtained of 0.314 or 31.4%, thus it can be said that the effect of the effectiveness of the application of government accounting standards on the quality of financial statements is 31.4%, which means that it is very influential.